Latest advances in postpartum hemorrhage management. Issue 1 (May 2022) - Kumaraswami, Sangeeta; Butwick, Alexander
Abstract : Hemorrhage is the leading cause of maternal mortality worldwide. A maternal health priority is improving how healthcare providers prevent and manage postpartum hemorrhage (PPH). Because anesthesiologists can help facilitate how hospitals develop approaches for PPH prevention and anticipatory planning, we review the potential utility of PPH risk-assessment tools, bundles, and protocols. Anesthesiologists rely on clinical and diagnostic information for initiating and evaluating medical management. Therefore, we review modalities for measuring blood loss after delivery, which includes visual, volumetric, gravimetric, and colorimetric approaches. Point-of-care technologies for assessing changes in central hemodynamics (ultrasonography) and coagulation profiles (rotational thromboelastometry and thromboelastography) are also discussed. Anesthesiologists play a critical role in the medical and transfusion management of PPH. Therefore, we review blood ordering and massive transfusion protocols, fixed-ratio vs. goal-directed transfusion approaches, coagulation changes during PPH, and the potential clinical utility of the pharmacological adjuncts, tranexamic acid, and fibrinogen concentrate.